Management of Advanced Ovarian Cancer: Current Clinical Practice and Future Perspectives - Dimitrios Papageorgiou; Galateia Liouta; Evangelia Pliakou; Eleftherios Zachariou; Ioakeim Sapantzoglou; Ioannis Prokopakis; Emmanuel N. Kontomanolis (Biomedicines, 2025)
Ovarian cancer is the most lethal gynecologic malignancy, which causes 313,959 new cases and 207,252 deaths worldwide annually. The lack of specific symptoms, together with no effective screening tools, results in 75% of patients receiving their diagnosis at an advanced stage. The combination of cytoreductive surgery with platinum-based chemotherapy plays a pivotal role in the treatment of advanced epithelial ovarian cancer, but patients still experience poor long-term survival because of frequent relapses and chemotherapy resistance. The treatment landscape has evolved because bevacizumab and Poly-ADP Ribose Polymerase inhibitors now serve as frontline and maintenance therapies for homologous recombination-deficient tumors. Treatment decisions for recurrent disease depend on platinum sensitivity assessment, which determines the appropriate therapeutic approach, while targeted agents deliver significant benefits to specific patient groups. The development of antibody-drug conjugates such as mirvetuximab soravtansine and immunotherapy, including checkpoint inhibitors and cancer vaccines, demonstrates promising investigative potential. The precision of therapy improves through the use of emerging biomarkers and molecular profiling techniques. The future management of this disease may change because of innovative approaches that include adoptive cell therapy, cytokine therapy, and oncolytic viruses. The progress made in ovarian cancer treatment still faces challenges when it comes to drug resistance, survival improvement, and life quality preservation. The development of translational research alongside clinical trials remains essential to bridge treatment gaps while creating personalized therapies based on molecular and clinical tumor characteristics.